FENOMENA NYAMUK DALAM KARYA LUKIS KONTEMPORER - DONI SISWANTO, Yasrul Sami, S. Sn, M. Sn, Drs. Muzni Ramanto (Serupa The Journal of Art Education, 2013)
Mosquitoes are the types of animals that people complain about, where mosquitoes are a nuisance animal, who preyed on human blood. This work aims at knowledge of mosquito that can be said, like a mosquito to human interaction phenomena, nature and the Creator. This work is visualized in a variety of mosquito occurrence in everyday life with the contemporary style of painting. In this final masterpiece the author prefers objects with lots of mosquitoes using a flat background. Mosquito objects as subject matter deliberately fox author, not like the original because that's where the author plays ideas and concepts work. The author is not too much to fill the empty space in the background which become habits authors paint. Key word: mosquito, Contemporary